Sustained LFA-1 cluster formation in the immune synapse requires the combined activities of L-plastin and calmodulin - Wabnitz, Guido H.; Lohneis, Philipp; Kirchgessner, Henning; Jahraus, Beate; Gottwald, Susan; Konstandin, Mathias; Klemke, Martin; Samstag, Yvonne (European journal of immunology, 2010)
Formation of immune synapses (IS) between T cells and APC requires multiple rearrangements in the actin cytoskeleton and selective receptor accumulation in supramolecular activation clusters (SMAC). The inner cluster (central SMAC) contains the TCR/CD3 complex. The outer cluster (peripheral SMAC) contains the integrin LFA-1 and Talin. Molecular mechanisms selectively stabilizing receptors in the IS remained largely unknown. Here, we demonstrate that sustained LFA-1 clustering in the IS is a consequence of the combined activities of the actin-bundling protein L-plastin (LPL) and calmodulin. Thus, upon antigen-recognition of T cells, LPL accumulated predominantly in the peripheral SMAC. siRNA-mediated knock-down of LPL led to a failure of LFA-1 and Talin redistribution - however, not TCR/CD3 relocalization - into the IS. As a result of this LPL knock-down, the T-cell/APC interface became smaller over time and T-cell proliferation was inhibited. Importantly, binding of calmodulin to LPL was required for the maintenance of LPL in the IS and consequently inhibition of calmodulin also prevented stable accumulation of LFA-1 and Talin, but not CD3, in the IS.
Gesehen am 19.09.2023